1999
DOI: 10.1088/0953-2048/12/5/001
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-based HTS thin films, processing, properties and applications

Abstract: Thin films of the Tl-based high-temperature superconducting (HTS) phases are beginning to find application in a number of practical devices, especially in the field of microwave communication systems. This review describes the issues surrounding the fabrication of thin films of the thallium-based HTS materials. The influence of thermodynamics and kinetics, the various potential thalliation techniques and the selection of an appropriate substrate material are all important considerations when designing a proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 217 publications
1
24
0
Order By: Relevance
“…1b). It has been suggested that the Tl-1212 phase may be formed by annealing at low thallous oxide partial pressures [11]. The measured values of the critical temperatures of the prepared samples were comparable (Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…1b). It has been suggested that the Tl-1212 phase may be formed by annealing at low thallous oxide partial pressures [11]. The measured values of the critical temperatures of the prepared samples were comparable (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…In open system, the formation path for the Tl-2223 phase implies Tl-2201 and Tl-2212 intermediates according to the sequence: precursor → Tl-2201 → Tl-2212 → Tl-2223 [11,12]. For the growth of the Tl-2223 phase annealing at higher temperatures and lower Tl content in the source pellet is necessary [11]. • C / 45 min using pellet B.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate plays a key role in the microstructural development of the grown film and hence in determining its superconducting properties [1]. Monocrystalline MgO and CeO 2 buffered R-plane sapphire were chosen for the fabrication of Tl-based superconducting thin films.…”
Section: Resultsmentioning
confidence: 99%
“…Especially thin films prepared on appropriate substrates can be used in applications ranging from passive microwave devices and active Josephson-effect devices to fundamental study of superconducting state [1]. Because of high toxicity and volatility of thallium at elevated temperatures, the synthesis of the thin films is realized in two steps.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the film fabrication process are described elsewhere. 10 The films were patterned by a combination of photolithography ͑using Shipley S1805 resist͒ and etching in dilute acetic acid ͑0.05 M͒. Finer features ͑including the 10 m wide bridges used in the experiments͒ were defined by direct laser micromachining of the film.…”
mentioning
confidence: 99%